Adsorption and transformation of thioarsenite at hematite/water interface under anaerobic condition in the presence of sulfide. (May 2019) - Wang, Ying; Lin, Jinru; Wang, Shaofeng; Zhang, Danni; Xiao, Fan; Wang, Xin; Jia, Yongfeng
Abstract: The adsorption behavior of thioarsenite (TAs III ) on the surface of hematite (α-Fe2 O3 ) is unknown at present. In the present study, we have investigated the transformation and reactions of TAs III [monothioarsenite (MTAs III ) and dithioarsneite (DTAs III )] on the surface of α-Fe2 O3 in the presence of sulfide at S/As = 1 and 3 by X-ray absorption spectroscopy (XAS) and Raman spectroscopy. The adsorption envelopes reveal that the adsorption of TAs III on α-Fe2 O3 is significantly less than that of arsenite (As III ) in the pH range from 7 to 11 with the initial As concentration of 25 mg L −1 . However, at the initial As concentration of 135 mg L −1, the uptake of TAs III by α-Fe2 O3 is higher at pH 7 but lower at pH 8–11 than that of As III . The adsorption isotherms show that the adsorption of As on α-Fe2 O3 is largely inhibited by the presence of aqueous sulfide at pH 7 with low As equilibrium concentration (<40 mg L −1 ). Whereas the uptake of As by α-Fe2 O3 is highly elevated compared with the value predicted by Langmuir model at pH 7 with high As equilibrium concentration (>40 mg L −1 ), implying the formation of As-bearing (surface) precipitate. The As and S K -edge XAS as well as Raman spectroscopy confirm the formation of As sulfide precipitate on the surface of α-Fe2 O3 in MTAs III system. It is worth to note that the oxidation of (thio)As III occurs on the surface of α-Fe2 O3 in DTAs III system under strictly anaerobic conditions. These results shed new light on the understanding of the interfacial behavior of As and point to the potential implication in immobilization and removal of arsenic in sulfidic environment. Highlights: The formation of thio-As III inhibits As adsorption on hematite at low As loading. The generated orpiment increases As uptake by hematite at high As loading. The oxidation of (thio)As III to (thio)As V occurs on hematite at S -II /As III  = 3.